9(x+-1)+-9(x+3)=1

Simple and best practice solution for 9(x+-1)+-9(x+3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+-1)+-9(x+3)=1 equation:


Simplifying
9(x + -1) + -9(x + 3) = 1

Reorder the terms:
9(-1 + x) + -9(x + 3) = 1
(-1 * 9 + x * 9) + -9(x + 3) = 1
(-9 + 9x) + -9(x + 3) = 1

Reorder the terms:
-9 + 9x + -9(3 + x) = 1
-9 + 9x + (3 * -9 + x * -9) = 1
-9 + 9x + (-27 + -9x) = 1

Reorder the terms:
-9 + -27 + 9x + -9x = 1

Combine like terms: -9 + -27 = -36
-36 + 9x + -9x = 1

Combine like terms: 9x + -9x = 0
-36 + 0 = 1
-36 = 1

Solving
-36 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x+5=7x-6 | | 159=568y | | (x^2/27.5)+x-55=0 | | x+35+x+15+2x-20+2x+x=360 | | 13/4-5/6 | | 14769=8457y | | 8x+y=-15 | | 1/4x2/2 | | 19263827364872365+1-1-1-1-1-1-1-1-1-1-2109742938647782364874635872643587645y=1 | | 1=4-2 | | 9(x-1)-9(x+3)=1 | | h=16t^2+64t+192 | | 1=y | | (-1/(x+1))-(2/(x-1))=(3/(x^2-1)) | | 43289767543769852346785347685346782437865672678254768925486792546789254678254678234567854278692435786345786923457869542786254386794578y=1 | | 2x+6+18/2=19 | | 1/3+1/6+(1/4-1/8) | | 3x+14=83 | | x+10+2+x+x=83 | | 83296587237658745687465y+8374=9384898365-375 | | 12y-1=3y-8 | | (1/2+1/3)-(1/4+1/5) | | 1+3+4+67-3-2-45-3+3y=1+938+934+23+23-23 | | -7=0.5(12s-2)-2s | | y^2-4x-2y=3 | | -7=50(12s-2)-2s | | 1/5x^2(20x^2-15x+3) | | 4x^2+16+23=0 | | 2(s+7)-s=1 | | 5x^2/5.1x10^-6 | | 20+5x=-2x-8 | | 2(v-4)=8v-14 |

Equations solver categories